Cell-free fat extract promotes axon regeneration and retinal ganglion cells survival in traumatic optic neuropathy - Sun, Yiyu; Chen, Di; Dai, Tao; Yu, Ziyou; Xie, Hui; Wang, Xiangsheng; Zhang, Wenjie (Frontiers in Cellular Neuroscience, 2024)
Injuries to axons within the central nervous system (CNS) pose a substantial clinical challenge due to their limited regenerative capacity. This study investigates the therapeutic potential of Cell-free fat extract (CEFFE) in CNS injury. CEFFE was injected intravitreally after the optic nerve was crushed. Two weeks post-injury, quantification of regenerated axons and survival rates of retinal ganglion cells (RGCs) were performed. Subsequently, comprehensive gene ontology (GO) an-notation elucidated the cellular origins and functional attributes of CEFFE components. Molecular mechanisms underlying CEFFE's therapeutic effects were explored through Western blotting (WB). Additionally, levels of inflammatory factors within CEFFE were determined using enzyme-linked immunosorbent assay (ELISA), and histological staining of microglia was conducted to assess its impact on neuroinflammation. CEFFE demonstrated a significant capacity to promote axon regeneration and enhance RGCs survival. GO annotation revealed the involvement of 146 proteins within CEFFE in axonogenesis and neurogenesis. WB analysis unveiled the multifaceted pathways through which CEFFE exerts its therapeutic effects. Elevated levels of inflammatory factors were detected through ELISA, and CEFFE exhibited a modulatory effect on microglial activation in the retinal tissue following optic nerve crush (ONC). The present study highlights the therapeutic promise of CEFFE in the management of CNS injuries, exemplified by its ability to foster axon regeneration and improve RGCs survival.